Model law against trafficking in persons (United Nations Publications, 2009)
Annotation. The publication was developed by the United Nations Office on Drugs and Crime (UNODC) in response to the request of the General Assembly to the Secretary-General to promote and assist the efforts of Member States to become party to and implement the United Nations Convention against Transnational Organized Crime and the Protocols thereto. It was developed in particular to assist States in implementing the provisions contained in the Protocol to Prevent, Suppress and Punish Trafficking in Persons, Especially Women and Children, supplementing that Convention. The Model Law will both facilitate and help systematize provision of legislative assistance by UNODC as well as facilitate review and amendment of existing legislation and adoption of new legislation by States themselves. It is designed to be adaptable to the needs of each State, whatever its legal tradition and social, economic, cultural and geographical conditions.